2005
DOI: 10.1124/jpet.105.094433
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Activation of Akt and Consequent Inhibition of Glycogen Synthase Kinase-3 by Brain-Derived Neurotrophic Factor and Insulin-Like Growth Factor-1 in Cultured Hippocampal Neurons

Abstract: Brain-derived neurotrophic factor (BDNF) and insulin-like growth factor-1 (IGF-1) seem to play key roles in mediating neuronal plasticity in the hippocampus. In the current studies, we have used cultured hippocampal neurons to study possible interactions between the two growth factors in modulating neuronal signaling pathways. BDNF and IGF-1 were found to each effectively activate the neuroprotective Akt pathway, with the magnitude of activation being at least additive when cultures were simultaneously treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 29 publications
2
48
1
2
Order By: Relevance
“…Moreover, further increasing Akt by combining FGF-2 with either IGF-1 or BDNF led to no further enhancement of neuroprotection. This is in contrast to our previous findings that IGF-1 and BDNF cumulatively enhance cell survival, in addition to cumulatively activating Akt (Johnson-Farley et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Moreover, further increasing Akt by combining FGF-2 with either IGF-1 or BDNF led to no further enhancement of neuroprotection. This is in contrast to our previous findings that IGF-1 and BDNF cumulatively enhance cell survival, in addition to cumulatively activating Akt (Johnson-Farley et al, 2006).…”
Section: Discussioncontrasting
confidence: 99%
“…We therefore sought to determine whether differences in the pattern of activation of these 2 kinases could account for the increased efficacy of FGF-2 vs. IGF-1 and BDNF in inducing neuroprotection. We have previously reported that maximal activation of ERK and Akt by IGF-1 and BDNF is stimulated by 100 ng/ml and 20 ng/ml concentrations, respectively (Johnson-Farley et al, 2006). The magnitude of IGF-1-and FGF-2-stimulated activation of Akt were found to be comparable (figure 4).…”
Section: Fgf-2 Stimulates Neuronal Survivalmentioning
confidence: 66%
See 3 more Smart Citations